2020
DOI: 10.3389/fmicb.2020.01405
|View full text |Cite
|
Sign up to set email alerts
|

Denosumab Regulates Gut Microbiota Composition and Cytokines in Dinitrobenzene Sulfonic Acid (DNBS)-Experimental Colitis

Abstract: The pro-inflammatory mediator receptor activator of nuclear factor-kappa B ligand (RANKL) plays a significant role in the development of rheumatoid arthritis; however, its role in inflammatory bowel disease is unknown. Genome-wide association metaanalysis for Crohn's disease (CD) identified a variant near the TNFSF11 gene that encodes RANKL and CD risk allele increased expression of RANKL in specific cell lines. This study aims to elucidate if the RANKL inhibitor denosumab can reduce the severity of experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 87 publications
0
9
0
Order By: Relevance
“…However, very little is known regarding any connection between the use of Denosumab on the human gut microbiome and how this interaction may affect overall bone health and healing. Nevertheless, there is indirect evidence based on a recent animal study by Khafipour et al in mice with colitis, which demonstrated differing microbial diversity in mice treated with Denosumab [167]. Although the results have no direct bearing on bone homeostasis, the effects of Denosumab on bone health may either be enhanced or suppressed based on alterations in the gut microbiota.…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%
“…However, very little is known regarding any connection between the use of Denosumab on the human gut microbiome and how this interaction may affect overall bone health and healing. Nevertheless, there is indirect evidence based on a recent animal study by Khafipour et al in mice with colitis, which demonstrated differing microbial diversity in mice treated with Denosumab [167]. Although the results have no direct bearing on bone homeostasis, the effects of Denosumab on bone health may either be enhanced or suppressed based on alterations in the gut microbiota.…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%
“…Catecholamine norepinephrine increases cardiac MMP-2 activity and collagen deposition [ 104 ], thus indicating that adrenergic receptors’ activation enhances MMP activity. In fact, the antagonist of β-adrenergic receptors, nebivolol, attenuates hypertension-induced vascular remodeling and increases vascular MMP-2 activity [ 105 ]. Similar effects are also reported in the hearts of hypertensive animals [ 106 ].…”
Section: Imbalanced Vascular Mmp Activity Activates Critical Mechanisms Leading To Vascular Remodeling In Hypertensionmentioning
confidence: 99%
“…MMP-2 and MMP-9 are also responsible for activating cytokines, such as transforming growth factor-β (TGF-β), which are involved in collagen accumulation and profibrotic alterations in remodeling that are associated with hypertension [ 105 ]. Tumor necrosis factor-α (TNF-α) is another cytokine implicated in the vascular remodeling of hypertension, as it is essential for Ang-II-induced MMP-2 expression [ 107 ].…”
Section: Imbalanced Vascular Mmp Activity Activates Critical Mechanisms Leading To Vascular Remodeling In Hypertensionmentioning
confidence: 99%
“…Inhibition of RANKL may have an additional impact on skeletal muscle with early clinical data showing a reduction in the risk of falls and improved markers of sarcopenia in elderly patients [ 160 ]. Additionally, Denosumab was recently found to reduce colonic expression of pro-inflammatory cytokines and modulate disruption of the microbiome in a murine model of colitis mimicking CD [ 161 ], suggesting a potential role for RANKL in disease pathogenesis. Despite this, Denosumab remains relatively unexplored in IBD and further investigation of its impact on bone, muscle and disease outcomes in pre-clinical and human IBD studies is required.…”
Section: Future Directionsmentioning
confidence: 99%